SOLIDARITY UNDER ÉMILE DURKHEIM’S THEORY AND ITS (IN)COMPATIBILITY WITH INTERNATIONAL LAW - Motte-Baumvol, Julia; Braga Guimarães, Gabriel (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2025)
Due to its capacity to unite diverse perspectives towards a shared objective, solidarity has become a crucial element in tackling transnational challenges. Among the many scholars who have delved into the examination of solidarity as a social phenomenon, the work of Émile Durkheim stands out. Considering the analysis conducted in Durkheim’s work is based on human individuals, one can wonder if the concepts of solidarity developed by the French scholar are compatible with interstate relations and, therefore, to what extent they foster the development of solidarity in the international law framework. This paper aims to analyze the compatibility of Émile Durkheim's theory concerning solidarity with the specificities of international Law. By acknowledging the limitations and challenges of Durkheim’s theory, this research aims to contribute to a more precise and effective understanding of solidarity within the international legal framework. The article first examines Durkheim's conceptualization of solidarity. It then assesses how this theory aligns with the unique characteristics of applying solidarity in interstate relations. The conclusion highlights that Durkheim's theory encounters challenges when directly applied to relations regulated by international law. The legal delineation of solidarity is still a work in progress within this branch of law, leaving ambiguity regarding what it means and in which situations it is to be applied. To sum up, this study emphasizes the growing significance of solidarity in international law and the necessity for a critical examination of Émile Durkheim's theory within the context of interstate relations.